Anti‐inflammatory effect of omega unsaturated fatty acids and dialysable leucocyte extracts on collagen‐induced arthritis in DBA/1 mice - Pérez‐Martínez, Pamela I. (Int J Exp Pathol, 2020)
Rheumatoid arthritis is a disabling autoimmune disease with a high global prevalence. Treatment with disease‐modifying anti‐arthritic drugs (DIMARDs) has been routinely used with beneficial effects but with adverse long‐term consequences; novel targeted biologics and small‐molecule inhibitors are promising options. In this study, we investigated whether purified omega unsaturated fatty acids (ω‐UFAs) and dialysable leukocyte extracts (DLEs) prevented the development of arthritis in a model of collagen‐induced arthritis (CIA) in mice. We also investigated whether the transcription factor NF‐κB and the NLRP3 inflammasome were involved in the process and whether their activity was modulated by treatment. The development of arthritis was evaluated for 84 days following treatment with nothing, dexamethasone, DLEs, docosahexaenoic acid, arachidonic acid, and oleic acid. Progression of CIA was monitored by evaluating clinical manifestations, inflammatory changes, and histological alterations in the pads’ articular tissues. Both DLEs and ω‐UFAs led to an almost complete inhibition of the inflammatory histopathology of CIA and this was concomitant with the inhibition of NF‐kB and the inhibition of the activation of NLRP3. These data suggest that ω‐UFAs and DLEs might have NF‐κB as a common target and that they might be used as ancillary medicines in the treatment of arthritis.